A ENFERMAGEM NA HISTÓRIA DE CONSTITUIÇÃO DAS ESCOLAS FORMADORAS DE TRABALHADORES DE SAÚDE - Freitag, Vera L.; Arboit, Jaqueline; Ubessi, Liamara D.; Mattos, Carine M. Z. d.; Righi, Liane B.; Stumm, Eniva M. F. (Salão do Conhecimento, 2013)
Resumo